Redesigning a fast-moving consumer goods supply chain considering social responsibility and logistical restrictions: case study in an Iranian food company - Sedehzadeh, Samaneh; Seifbarghy, Mehdi (Environmental science and pollution research international, 2021)
Redesigning a supply chain network is an important strategic problem which affects network productivity, especially in varying environments. We propose a novel mathematical model for redesigning the network of a real company considering economic and social aspects. Strategic decisions of the model consist of opening new centers, selecting capacities from a set of discrete sizes, and closing or expanding capacities of existing centers during a planning horizon. Tactical decisions are involved with determination of product flows, facilities allocation, selection of fleet modes in terms of product types (i.e., frozen, chilled, dry, and ready meal) and fleet ownership types (i.e., self-owned or leased). The correlations and restrictions involved with multi-product supply chains, such as substitutability of products, the impossibility of transportation of some products together because of chemical effects or legal restrictions, and necessity of allocation of special fleets to some products because of specific holding conditions, are considered. Noting social responsibility aspect, an objective of this model is to minimize the maximum unsatisfied demand of added food banks to the network whose roles are feeding needy people. An interactive fuzzy programming approach is applied to solve the given bi-objective problem. Finally, useful managerial insights are derived from the results which show that more geographical diversity of facilities, using a new distribution strategy, and adding food banks as a new echelon can increase the productivity of the given network and makes it more responsible in terms of social responsibility.